Improving Quality Of Service by Comparison and Evaluation Performance Of SC-AC and MC-AC in Wireless - K. Salih, Ghaidaa (Journal of Engineering and Sustainable Development, 2014)
The main aim of this paper is analysis and modeling different types of call admission control, using Multi Cell admission control algorithms (MC-AC) algorithm in the communication systems over using Single-Cell Admission Control (SC-AC). The analysis of the technical issues that is related to communication systems will help the operators in the field of telecom sector, in some way that provides the ability to improve the quality of service of the communication system. The simulation model takes into consideration the effect of multipath fading and signal to interference noise ratio that degrades the quality of the service, and it shows that the diversity techniques is a very important technique to deal with multi path fading channels. The traffic model of this paper expands the performance of three types of service classes: the voice calls, multimedia, and video. The class services were categorized to real time and non-real time services upon the priority of the service.